Penerapan Sistem Pakar Untuk Mendeteksi Dini Gangguan Sistem Pencernaan Pada Anak Menggunakan Metode Inferensi Forward Chaining Dan Penentuan Tingkat Kepastiannya Menggunakan Certainty Factor - Ramadhan, Novreza; Djesmedi, Dinda; Rindhani A, Mellya; Firdalius, Fitri (Jurnal Sains Informatika Terapan, 2025)
The digestive system is the most important organ in the human body, especially in children. Food and drinks that enter a child's body will become a source of nutrition for the child's growth and development. In this day and age, there are still many parents who pay little attention to food hygiene and carelessly give food to their children, causing digestive problems in children. Parents' lack of knowledge about the symptoms of digestive disorders means that parents do not know what to do for quick treatment to overcome the problem of digestive disorders. With this expert system, it is hoped that it can help parents recognize the symptoms of digestive disorders and be able to treat them quickly. This expert system was created using the Forward Chaining inference method and determining the level of certainty using the Certainty Factor method. The Forward Chaining method is an approach used to conclude information based on facts that have been previously collected. Meanwhile, the Certainty Factor method works by reasoning like an expert and then showing the value of a measure of certainty regarding a fact to obtain a trust value. The result of this research is the formation of an expert system for diagnosing digestive disorders in children so that it can make it easier for parents to get information about the symptoms of digestive disorders in children and can provide quick treatment anywhere and anytime.